2012
DOI: 10.3892/or.2012.1765
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 and Sox2 are overexpressed in human neuroblastoma and inhibited by chemotherapy

Abstract: Abstract. Neuroblastoma (NB) is the most common extracranial solid tumor in childhood and the most frequently diagnosed neoplasm during infancy. Oct4 and Sox2 are essential transcription factors for embryonic development and play key roles in determining the fate of stem cells. In this study, we aimed to investigate the expression of Oct4 and Sox2 in NB tissues, and evaluated their relationship with various clinicopathological parameters. Oct4 and Sox2 expression in 65 samples of NB and paracancerous tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Our results show alterations not only in POU5F1 but also in members of TGF-β, Notch and Wnt signalling pathways indicating the potential of this gene to be used as a new therapeutical target. Our findings are supported by other works that described its potential in other tumors [62], [64], [67] and as a possible new CSC marker in neuroblastoma [67][69].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results show alterations not only in POU5F1 but also in members of TGF-β, Notch and Wnt signalling pathways indicating the potential of this gene to be used as a new therapeutical target. Our findings are supported by other works that described its potential in other tumors [62], [64], [67] and as a possible new CSC marker in neuroblastoma [67][69].…”
Section: Discussionsupporting
confidence: 91%
“…POU5F1 was described in several tumors (urothelial, prostatic, cervical, breast and lung) and is implicated in different functions as chemoresistance, prognosis marker, proliferation, apoptosis, migration and invasion [58][61]. In addition to all these functions, this gene plays an important role in stemness and self-renewal of stem cells in normal and tumor tissues [60], [62], [63] and was found to be overexpressed and correlated with the progression of neuroblastoma [64]. This gene could interact with members from other pathways as TGF-β, Notch and Wnt [65], [66] working together in the regulation of stem cell pluripotency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the BMP4 pathway is involved in mammalian palatogenesis [71], and mutations in BMP4 have been associated with human NSCL/P [12], [58], [59]. Research has shown that OCT4 is overexpressed in cancer cell lines and in diverse cancer entities [24], [37], [67], suggesting that aberrant transcriptional regulation of OCT4 might be a mechanism in cancer susceptibility. Thus, a plausible hypothesis is that rs6457327 regulates OCT4 expression, and that this regulation is a possible common process in oncogenesis and the development of NSCL/P.…”
Section: Discussionmentioning
confidence: 99%
“…OCT4-expressing cancer cells show increased tumorigenicity and high resistance to chemotherapeutics (13). The expression of OCT4 is upregulated in neuroblastoma; however, it is inhibited by chemotherapy (14), suggesting that it may be a new target for identifying candidate antitumor drugs. Therefore, OCT4 may be important in carcinogenesis and may provide one possible mechanism by which cancer cells acquire a drug-resistant phenotype (15).…”
Section: Introductionmentioning
confidence: 99%